Análise do perfil metabolômico do ameloblastoma - André Myller Barbosa Silva (2019)
Ameloblastoma is a benign tumor that originates from the odontogenic epithelium. The pathogenesis is not completely understood and involves genetic alterations such as the mutation of the BRAF gene. Since the lesion presents locally infiltrative behavior and a high potential to local recurrences, the treatment usually requires total surgical excision of the lesion, resulting in facial deformity, great morbidity and, consequently, a significant impact on the life of the affected patient. The metabolomics represents the study of the metabolites set of a biological system. It provides final information more closely related to the studied phenotype regarding the interactions involving genetic alterations, enzymatic activity and metabolic reactions. The use of formalin-fixed and paraffin-embedded samples has been shown to be convenient in metabolomics experiments because it represents an abundant source of biological material for research and for demonstrating reliability in its use. Thus, the aim of this study was to evaluate the metabolic profile of ameloblastoma and to identify metabolic pathways possibly involved in the pathogenesis and progression of this lesion, as well as to corelate these findings to the presence of BRAF-V600E mutation. The study was approved by the Research Ethics Committee of the Universidade Federal de Minas Gerais under CAAE number 97428718.5.0000.5149. Fourteen formalin-fixed and paraffin-embedded tumor samples and 6 samples of morphologically normal odontogenic epithelium obtained from dental follicles were used. Metabolites were identified by gas chromatography coupled to mass spectrometry and the presence of the BRAF-V600E mutation was assessed by real-time PCR. The data was submitted to univariate and multivariate statistical analyses. Eleven metabolites were found to be significantly higher in ameloblastoma compared to dental follicles, including amino acids, fatty acids, carbohydrates, inorganic acids and organoheterocyclic compounds. The presence of the BRAF-V600E mutation in the samples was related to decreased levels of glycerol compared to tumors bearing only wild-type alleles of this gene. No metabolic differences were observed between recurrent ameloblastomas and primary ameloblastomas. It is concluded that ameloblastoma presents a different metabolomic profile of morphologically normal odontogenic tissue and that the BRAF-V600E mutation may contribute to some metabolic alterations present in the ameloblastoma, which may be related to the pathogenesis of this tumor.